Changes in seismicity and stress loading on subduction faults in the Kanto region, Japan, 2011–2014. Issue 4 (30th April 2015) - Gardonio, Blandine; Marsan, David; Lengliné, Olivier; Enescu, Bogdan; Bouchon, Michel; Got, Jean‐Luc
Abstract Seismic activity has increased in the Kanto region, Japan, following the 2011 M9.0 Tohoku earthquake. We here reassess this increase up to June 2014, to show that normal, Omori‐like relaxation characterizes the activity on crustal faults as well as on the Philippine Sea plate, but not on the deeper Pacific plate. There repeating earthquakes display a twofold rate of occurrence (still ongoing in June 2014) as compared to the pre‐Tohoku rate, suggesting enhanced creep. We compute the Coulomb stress changes on the upper locked portion of the Philippine Sea plate, which last ruptured in 1923. We find that this fault was little affected by either the coseismic, the postseismic, the accelerated creep, or the 2011 Boso silent slip event.